Visibility of women in the software development life cycle - Negrier, Marlene (2023)
The visibility of women in the labor context of software production is very weak, due to their low participation and socio-cultural difficulties to grow in the labor context. This article aims to show women's role and contribution in the whole life cycle of software development and thus promote gender equity and equality in this area. Methodologically, we have taken the systematic mapping technique to search in the technical literature as a basis. This allows us to obtain a comprehensive view of the work related to gender gaps women face in their work performance in software manufacturing. To complement this study, a form including closed questions was designed to obtain information about the role women play in software production and their expectations in terms of their professional contribution in this field. The main findings allow us to infer that there are biases when defining leaders and roles in software development. It is hoped that the findings of this study will provide inspiring information for women who wish to lead teams in the field of software development by showing the reduction of gender gaps and the possibility of successfully exercising leadership in this field.